Recent status of bowhead whales, Balaena mysticetus, in the wintering grounds off West Greenland - Reeves , Randall R.; Heide-Jørgensen , Mads Peter (Polar Research, 1996)
Bowhead whales, Balaena mysticetus, belonging to the Davis Strait/Baffin Bay stock, have historically in Baffin Bay and Davis Strait, including waters along the west coast of Greenland in and near the entrance of Disko Bay. Aerial surveys of the Disko Bay region during late winter (1981, 1982, 1990,1991, 1993 and 1994) showed that it was still visited regularly by a few tens of whales. Commercial whaling on bowheads in Baffin Bay and Davis Strait ended in about 1915, but occasional killing continued until as recently as the 1970s. The low numbers of bowheads observed off West Greenland in recent years are consistent with the results of surveys of the summering grounds in the eastern Canadian Arctic, indicating that any recovery has been exceedingly slow. The only conclusion supported by the data is that the current stock size is a small fraction of what it was prior to commercial whaling.